Analisis Pemahaman Kebhinekaan dalam Menanamkan Rasa Toleransi pada Siswa Kelas V UPT SD Negeri 290 Gresik - Qur’ani, Hilda Mar’ah; Rozie, Fachrur (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the understanding of diversity in efforts to enhance the sense of tolerance among fifth-grade students at UPT SD Negeri 290 Gresik. Diversity, which includes ethnic, religious, racial, and cultural differences, is one of the essential pillars in building a harmonious and tolerant society. The research method used is a descriptive qualitative method, with data collection techniques including observation, interviews, and documentation. The subjects of this study are the fifth-grade students at UPT SD Negeri 290 Gresik, as well as the fifth-grade teachers at UPT SD Negeri 290 Gresik. The findings of this study are that the 5th grade students of UPT SD Negeri 290 Gresik are good at understanding the value of diversity and tolerance. They have been able and successful in applying it in their daily lives. They are also able to respect each other, unite and compact with their colleagues as well as in the surrounding environment